Price discrimination via the choice of distribution channels - Uwe Dulleck; Rudolf Kerschbamer (Johannes Kepler University of Linz, Department of Economics, 2005)
This article studies the use of different distribution channels as an instrument of price discrimination in credence goods markets. In credence goods markets, where consumers do not know which quality of the good or service they need, price discrimination proceeds along the dimension of quality of advice offered. High quality advice and appropriate treatment is provided to the most profitable market segment only. Less profitable consumers are induced to demand a treatment without a serious diagnosis. If consumers differ in the probabilities of needing different treatments some consumers are potentially overtreated. By contrast, under heterogeneity in the valuations of a successful intervention some consumers are potentially undertreated. Our results help to explain the casual observation that in the early phase of the IT industry only low quality equipment was distributed via warehouse sellers while today it is quite common to see high quality equipment at discounters.
Keywords: L15; D82; D40; 330; Price Discrimination; Distribution Channels; Credence Goods; Experts; Discounters; Preisdifferenzierung; Vertriebsweg; Produktqualität; Konsumentenverhalten; Theorie